Heavy metals contamination in geothermal medicinal plant extract; Chromolaena odorata Linn - A. Abubakar; H. Yusuf; M. Syukri; R. Nasution; M. Yusuf; R. Idroes (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Medicinal plants growing in geothermal areas have been reported to possess relatively high concentrations of bioactive secondary metabolites, which have been attributed to the adaptive heat stress response. Nonetheless, the exploitation of their medicinal benefits is limited by potentially life-threatening concentrations of heavy metals. Chromolaena odorata Linn, also called seurapoh, is a well-known medicinal plant that can absorb and accumulate heavy metals from the soil. This present study aimed to investigate the contents of mercury, lead, cadmium, and arsenic in the ethanolic extract of Chromolaena odorata Linn leaves collected from a geothermal area in Aceh Province, Indonesia.METHODS: Three hot springs, namely Ie-Suum, Ie-Jue, and Ie-Brouk, located in the same geothermal area, Seulawah Agam, were selected as the sampling points, and three samples of Chromolaena odorata were collected at each point. Extraction was carried out by means of maceration employing ethanol solvent. The heavy metal contents of each extract were determined using priorly validated atomic absorption spectrometry and graphite furnace atomic absorption spectrometry. The maximum thresholds of each heavy metal from the Indonesian Agency for Drug and Food Control were adopted during data interpretation.FINDINGS: The results revealed the presence of trace levels of arsenic (0.0482 ± 0.004 – 0.0639 ± 0.007 milligram per kilogram) and lead (0.0219 ± 0.004 – 0.0672 ± 0.006 milligram per kilogram), which did not exceed Indonesian maximum safety thresholds (≤5 and ≤10 milligram per kilogram, respectively). Mercury in all samples was not observable (limit of detection = 0.018 milligram per liter). Cadmium was observed in almost all samples with a concentration range of 0.0219 ± 0.005–1.1472 ± 0.006 milligram per kilogram, which exceeded the maximum threshold (0.3 milligram per liter).CONCLUSION: Heavy metal contamination in the ethanolic extract of geothermal Chromolaena odorata leaves has been attributed to volcanic activities. Among the heavy metals of concern, cadmium was the only one with a concentration exceeding the safety limit. The presence of cadmium in the extract at a high concentration could cause its translocation to the human body, eventually leading to multiple organ damage. Therefore, the extract of Chromolaena odorata leaves collected from a geothermal area should be consumed with caution for possible cadmium intoxication.